1996
DOI: 10.1177/019459989611500518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracellular Calcium on Cholesteatoma Migration and Adhesion in Vitro

Abstract: Cholesteatoma matrix and tympanic epithelia share the unique property of en mass migratory locomotion in vitro. Although this migratory behavior is not well understood, it is thought to be a major contributor to the pathogenesis and pathophysiology of cholesteatoma disease. We have surmised that en mass migration depends on tight calcium-dependent intercellular and substrate cellular adhesions. The purpose of this investigation was to determine the effects of a diminished extracellular calcium level on cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…If calcium is removed from cholesteatoma growth and migration stimulating culture media, there is a tenfold reduction in the degree of cholesteatoma migration. 15 Calcium is essential for cell to cell adhesion, for instance, between keratinocytes and substrate cells. These authors studied the in vitro inhibitory effects of all-trans retinoic acid on cholesteatoma migration in human cholesteatoma samples cultured in cell-growth simulating media.…”
Section: Discussionmentioning
confidence: 99%
“…If calcium is removed from cholesteatoma growth and migration stimulating culture media, there is a tenfold reduction in the degree of cholesteatoma migration. 15 Calcium is essential for cell to cell adhesion, for instance, between keratinocytes and substrate cells. These authors studied the in vitro inhibitory effects of all-trans retinoic acid on cholesteatoma migration in human cholesteatoma samples cultured in cell-growth simulating media.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then allowed to grow at 37°C in a humid atmosphere containing 5% carbon dioxide. Once growth and migration began, the rate of migration was measured (in millimeters) every 24 hours as previously described 7 . Migratory distances were determined by measuring the distance the center of each cell mass traveled every 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Ferlito et al 8 suggested that the destructive property of cholesteatomas, bone erosion, is caused by the collagenases produced by the components of squamous and fibrous epithelial tissues. The hypothesis of bone absorption by biochemical action exclusively done by collagenolitic enzimes was later incorporated by other agents, such as tumor necrosis factor (TNF), interleukins (IL-1a) and prostaglandins (PGE2) 9 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%